2006
DOI: 10.1063/1.2345909
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of Er(III) luminescence by ligand C–H vibrations: Implications for the use of erbium complexes in telecommunications

Abstract: The authors have quantified the quenching of the luminescence lifetime of Er 3+ ions in organic complexes due to the presence of CH vibrational oscillators as a function of their distance from the ion. They have shown that any hydrogen atoms within a sphere of at least 20 Å from an erbium ion will cause sufficient quenching to prohibit its use in telecommunications applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 13 publications
1
84
0
Order By: Relevance
“…However, when incorporated into solid hosts, the crystal field of the host induces a mixing of states, thus relaxing the selection rules. In matrices devoid of high-energy vibrations, particularly OH or NH, but also CH, [4] the Er( 4 I 13/2 ) lifetime is in the millisecond range and may even reach 24 ms. [5] This makes Erdoped materials attractive for laser and optical amplifiers operating at 1540 nm, which is one of the standard telecommunication wavelengths. Initially, these devices have mostly implied purely inorganic compounds such as silica, alumina or LiNbO 3 or nonoxide glasses as host matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when incorporated into solid hosts, the crystal field of the host induces a mixing of states, thus relaxing the selection rules. In matrices devoid of high-energy vibrations, particularly OH or NH, but also CH, [4] the Er( 4 I 13/2 ) lifetime is in the millisecond range and may even reach 24 ms. [5] This makes Erdoped materials attractive for laser and optical amplifiers operating at 1540 nm, which is one of the standard telecommunication wavelengths. Initially, these devices have mostly implied purely inorganic compounds such as silica, alumina or LiNbO 3 or nonoxide glasses as host matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Actually, the Er III ion exhibits a 4f intrashell transition from its first excited state 4 I 13/2 to the ground state 4 I 15/2 , which occurs at a wavelength of 1540 nm. Optical 4f intrashell transitions are partially forbidden in the free Er III ion.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallographic data and refinement parameters for the complexes are presented in Table 1 À ligand, it completes its coordination environment with one O atom from the monodentate NO 3 À anion and one O atom from the coordinated m 3 -OH À group. The unique Nd/Nd distances are different, with the distances of 3.6407(10) and 3.8757(11)-3.9782 (8) A for Nd1/ Nd2, Nd1/Nd1a and Nd2/Nd1a, respectively, in which each of the Nd1/Nd2 separations in the equivalent Nd 2 L(HL) moieties is slightly shorter than that (Nd1/Nd1a or Nd2/Nd1a separation) between two equivalent Nd 2 L(HL) moieties. For the inner Nd 3+ ion (Nd1 or Nd1a), the Nd-O bond length (2.414(7)-2.419 (6) A; O atoms from coordinated m 3 -OH À group) or the Nd-N bond lengths (2.477(8)-2.553(9) A) are in the range of the Nd-O bond lengths (2.382(6)-2.569 (7) A) with O atoms from the phenoxo groups.…”
Section: Methodsmentioning
confidence: 99%
“…5 We recently quantified the role of CH oscillators in the quenching of erbium by deuterating the ͓Cs͔͓Er͑HFA͒ 4 ͔ ͑H-HFA is 1,1,1,5,5,5-hexafluoro-2,4-pentanedione͒ system, which has only one C-H bond per ligand, and we showed that any hydrogen within 20 Å of an erbium ion acts as an efficient quenching center. 6,7 Mancino et al 8 have shown that an evaporated thin film of Er͑F-tpip͒ 3 , where F-tpip is perfluorinated imidodiphosphinate ͓͑C 6 F 5 ͒ 2 P͑O͔͒ 2 N − , has a luminescence lifetime of 224 s and this system, with no hydrogen, has a lifetime still considerably shorter than that expected for isolated ions. We have recently investigated the perfluorinated diphenylphosphinate system Er͓͑C 6 F 5 ͒ 2 PO 2 ͔ 3 , 9 which forms a thermally stable but highly insoluble coordination polymer, and found that in the as-grown state, we can obtain luminescence lifetimes of ϳ0.5 ms. Again, this is still significantly worse than might be expected from isolated ions and suggests that other quenching mechanisms are operating.…”
mentioning
confidence: 99%